OPTIMIZATION OF DIAGNOSIS AND TREATMENT OF LEUKOENCEPHALITIS IN CHILDREN: LABORATORY EXAMINATION METHODS - Niyozov Shukhrat Toshtemirovich; Khudoyberdiyeva Dilovar Imomnazarovna (Western European Studies, 2025)
This paper explores the advances in the diagnosis, treatment, and optimization of laboratory examination methods for leukoencephalitis in pediatric patients. Leukoencephalitis, a rare but serious condition characterized by inflammation of the white matter in the brain, can cause severe neurological impairment if not diagnosed and treated promptly. The article reviews the latest diagnostic techniques, including neuroimaging, cerebrospinal fluid analysis, and molecular diagnostics, as well as current treatment strategies, with a focus on improving outcomes for children
Keywords: Leukoencephalitis; pediatric treatment; laboratory diagnosis; optimization